Challenges and Competency Gaps in the Implementation of 21st Century Learning: Evidence from Junior High Schools in Ambon, Indonesia - Samanery, Risky Dahlan; Suyud (Belajea: Jurnal Pendidikan Islam, 2025)
Teacher competency in 21st-century learning is critically important, especially in public junior high schools in Ambon City, where teachers are expected to master four key competencies required for 21st-century instruction. Although numerous studies have explored teacher preparedness for 21st-century learning, a research gap remains regarding how these competencies evolve in island regions like Ambon, where geographic constraints and uneven access to educational resources shape instructional practices. This study aims to examine the extent of teacher competency, the obstacles encountered, and the efforts made by teachers, schools, and local governments to develop teacher proficiency in 21st-century learning. A qualitative descriptive approach was employed, involving interviews, documentation studies, and observations with teachers, principals, school supervisors, and the head of the education and educational personnel division of the local education office. Data were analysed using the interactive model developed by Miles, Huberman, and Saldaña. The findings reveal that teachers demonstrate adequate mastery of critical thinking, problem-solving, communication, and collaboration skills, but still show weaknesses in creative and innovative thinking competencies. Furthermore, four challenges were identified: limited supporting facilities and infrastructure, low initiative or motivation, constraints related to senior or less productive teachers, and heavy teaching workloads that hinder competency development. Additionally, efforts by teachers, schools, and local governments to enhance teachers’ competencies remain insufficient, particularly in 21st-century learning. These findings imply that strengthening teacher competency should be a priority in regional education policies and that they should contribute to the global discourse on the complexities of implementing 21st-century learning across geographically diverse contexts.